Experimental and numerical investigations of hydrodynamic response of biodegradable drifting Fish Aggregating Devices (FADs) in waves. (15th January 2022) - Wan, Rong; Zhang, Tongzheng; Zhou, Cheng; Zhao, Fenfang; Wang, Weijie
Abstract: Fish Aggregating Devices (FADs) are artificial floating objects deployed in tropical and subtropical pelagic oceans to attract tuna species for capture. Understanding the wave-induced drifting behavior can optimize the dynamical stability of drifting FADs in oceans and improve catchability. In this study, to investigate the dominant factors for stable performance and the validity of different drifting FADs the model experiments of hydrodynamic responses of 14 types of biodegradable drifting FADs models in heave motion and pitch motion are carried out in regular wave conditions. Numerical simulations of three of the models are implemented, and the experimental results are used to validate the results of the numerical simulations. In the numerical simulation, Reynolds-averaged Navier-Stokes (RANS) solver, a realizable k - ε model with two-layer, all y  + wall treatment and wave forcing method based on the Euler Overlay Method (EOM) for wave generating and wave absorbing are performed. The results show that the numerical results agreed well with the experimental values. The effects of wave steepness, relative length, relative width, cover object, hanging object, and weight of sinker on the FADs are analyzed. The results indicate that with the constant wave amplitude, the heave motion response increases significantly as the wave period increase, and opposed to the pitch motion response. Wave steepness, relative length, relative width, and the length of the FADs model have an important influence on the motion response amplitude operators (RAO) of the FADs. The FADs model constructed with netting panel and rope as cover object and hanging object, and weighted by a 2.00 kg sinker behaved the most stable behavior among all the models. This study can be used to find out the interaction between waves and the FADs and provide guidance on the design of high-performance biodegradable FADs with stabilization and a long lifespan in harsh pelagic ocean environments. Highlights: Experimental tests are performed of the hydrodynamic performance of biodegradable FADs subjected to regular waves. The Optotrak Certus optical tracking system, heave and pitch motions are recorded. The experimental results are compared with the numerical simulations and a good agreement is achieved. The wave factors and structural parameters have great effect on the hydrodynamic performance of FADs.